Aktivitas Daya Hambat Isolat Actinomycetes dengan Lama Fermentasi yang Berbeda terhadap Pertumbuhan Klebsiella pneumoniae - Insani, Annisa Nur; Bahar, Meiskha; Nugrohowati, Nunuk; Yulianti, Retno (Jurnal Kesehatan Andalas, 2022)
Actinomycetes are filamentous, Gram-positive bacteria widely distributed in soil and can produce secondary metabolites useful as antibiotics. The synthesis of secondary metabolites of Actinomycetes is influenced by the growth conditions of each isolate, including the fermentation period. Klebsiella pneumoniae is an opportunistic bacterial pathogen causing lower respiratory tract infection. Objectives: To determined the inhibition activity of Actinomycetes with different fermentation periods against the growth of Â K.pneumoniae. Methods: Actinomycetes were isolated from soil in Kebun Raya Bogor and grown on Starch Casein Agar (SCA) medium before being fermented in liquid media consisting of 2% of mannitol, 2% of peptone, and 1% of glucose with an incubation time of 6,7, and 8 days. An antibacterial activity test was conducted on Mueller Hinton Agar (MHA) medium using the well diffusion method. Results: The activity of Actinomycetes isolates with fermentation duration of 6,7 and 8 were able to inhibit the growth of K. pneumoniae with an average inhibition zone of 4,46 mm; 4,94 mm; and 5,04 mm, respectively. Actinomycetes' inhibitory mechanism ranges from inhibition of cell wall synthesis to nucleic acid and protein synthesis. One Way ANOVA test showed significant differences between the inhibition zone produced by each fermentation group. Conclusion: Actinomycetes isolates have antibacterial activity against the growth of K. pneumoniae with the highest activity achieved by Actinomycetes with a fermentation time of 8 days.Keywords: Â Actinomycetes, antibacterial, fermentation, Klebsiella pneumoniae